2015
DOI: 10.1016/j.fertnstert.2015.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Antimüllerian hormone: prediction of cumulative live birth in gonadotropin-releasing hormone antagonist treatment for in vitro fertilization

Abstract: www.clinicaltrials.gov, NCT02309073.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 34 publications
2
19
0
2
Order By: Relevance
“…The results of the study demonstrated the good correlation between AMH level and oocyte yield, suggesting that AMH may be very effective in predicting oocyte yield in IVF treatment. It is important to note, however, that AMH is not a good predictor of pregnancy or pregnancy potential as reported elsewhere . AMH is an indicator reflecting the degree of primordial follicles remaining in the ovary, which is independent of whether fertilized oocytes can be developed in the uterus.…”
Section: Discussionmentioning
confidence: 76%
“…The results of the study demonstrated the good correlation between AMH level and oocyte yield, suggesting that AMH may be very effective in predicting oocyte yield in IVF treatment. It is important to note, however, that AMH is not a good predictor of pregnancy or pregnancy potential as reported elsewhere . AMH is an indicator reflecting the degree of primordial follicles remaining in the ovary, which is independent of whether fertilized oocytes can be developed in the uterus.…”
Section: Discussionmentioning
confidence: 76%
“…Thus, it appears that age could not be a strong prognostic success factor of IVF-ICSI for POR. These results are contradictory to those of numerous previous studies, which demonstrated that age is a strong determinant of the IVF pregnancy rate [7,8,13]. Santulli et al [14] demonstrated that age > 32 years was an important risk factor for endometriosis-related infertility (OR = 1.9; 95% CI 1.4-2.4).…”
Section: Discussionmentioning
confidence: 75%
“…Therefore, ‘Long infertility period’ and ‘Decreased ovarian reserve’ are hypothesized to reflect individual differences beyond age‐related fertility decline. Furthermore, serum anti‐Müllerian hormone level is generally considered superior to the serum FSH level as a predictor of the ovarian response, but these data suffer from insufficient samples for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To identify significant factors associated with outcomes of infertility treatments, we selected 10 pretreatment factors that have been investigated previously . These factors included the following: (i) ‘Advanced age’, defined as an age of 35 or older at the time each infertility treatment is initiated; (ii) ‘Secondary infertility’, defined as multiparous women with infertility; (iii) ‘Long infertility period’, defined as married patients who began infertility treatments after ≥24 months of unprotected and frequent intercourse; (iv) ‘Past treatment history’, defined as patients who were transferred from other hospitals; (v) ‘Decreased ovarian reserve’, defined as serum follicle‐stimulating hormone (FSH) levels greater than 10 mIU/ml in the early follicular phase; (vi) ‘Tubal infertility’, defined as obstructed fallopian tubes based on hysterosalpingography or hysteroscopy; (vii) ‘Male infertility’, defined as sperm abnormalities based on a semen analysis according to the World Health Organization criteria; (viii) ‘Uterine fibroid’, defined as a past history or current presence of uterine fibroid as judged by clinical images; (ix) the presence of ‘Advanced endometriosis;’ and (x) ‘Abdominal surgery history’.…”
Section: Methodsmentioning
confidence: 99%